(untitled) (Homiletic, 2023)
This issue of Homiletic includes a new feature, a "International Development in Homlietics." At the request of our readers, we will occasionally offer reviews of international development in homiletics to inspire, support, and/or challenge your work with students. We hope you enjoy our review by Alexander Deeg, Chair for Practical Theology and Dean of the Faculty Leipzig Universit.